Conduct of dental missions by the Philippine Dental Association Chapters in the National Capital Region - Hernandez, Shaliza d.J.; Javier, Ronilyne L.; Philippine Dental Association (Manila Department of Community Dentistry, University of the Philippines Manila, 2016)
INTRODUCTION: To help address the alarming oral health status among Filipinos, the local chapters of PDA provide free dental services to the underserved members of the community. This prompted the researchers to determine how the PDA-NCR chapters conduct their dental missions.
METHODS: Only 5 out of 16 PDA-NCR chapters agreed for an interview and 4 for an observation. A checklist of dental mission requirements adapted from the PDA Legislative Digest IV was used as a guide on what to look for during the observation. The participating chapters answered a 25-item interview guide the planning,conduct, evaluation and limitations of dental missions. The services offered during dental missions were identified. Awareness and compliance with PDA's "no extraction policy" were also asked.
RESULTS: There are written guidelines formulated by the PDA in conducting dental missions. The following services are offered: extraction, restorations, scaling, fluoride application, oral hygiene education and denture service. All chapters only perform cleaning and disinfection of instruments but not sterilization. The limitations identified were lack of the following: clean water, supplies, instruments, volunteers, funds; and high expectations of patients. The participating chapters were also aware of PDA's "no extraction policy in all dental missions" but they have poor compliance.
CONCLUSION:The participating chapters do not follow a universal guideline in planning, conducting and evaluating dental missions.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila
Keywords: Dental mission